2015
DOI: 10.1111/scs.12219
|View full text |Cite
|
Sign up to set email alerts
|

Conversations between persons with dementia disease living in nursing homes and nurses – qualitative evaluation of an intervention with the validation method

Abstract: Living with dementia disease (DD) can include difficulties describing experiences of everyday lives, which can lead to withdrawal, social isolation or existential homelessness. Persons with DD living in nursing homes are mainly dependent on the nurses for establishing and maintaining relationships with those around them. It can be challenging for nurses to understand what a person with DD is trying to express and to make themselves understood in turn. The validation method is intended to facilitate communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 36 publications
(57 reference statements)
0
30
0
8
Order By: Relevance
“…Eight detailed qualitative studies of training-interventions were available (Chenoweth et al, 2015;Figueiredo, Barbosa, Cruz, Marques, & Sousa, 2013;Hammar et al, 2011;Lykkeslet et al, 2014;Soderlund et al, 2013;Soderlund et al, 2016;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2016;Soderlund, Norberg, & Hansebo, 2012, 2014. As previously discussed the methodology and focus of these studies was diverse, and the quality was variable.…”
Section: Acceptability: Satisfaction and Qualitative Datamentioning
confidence: 99%
“…Eight detailed qualitative studies of training-interventions were available (Chenoweth et al, 2015;Figueiredo, Barbosa, Cruz, Marques, & Sousa, 2013;Hammar et al, 2011;Lykkeslet et al, 2014;Soderlund et al, 2013;Soderlund et al, 2016;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2016;Soderlund, Norberg, & Hansebo, 2012, 2014. As previously discussed the methodology and focus of these studies was diverse, and the quality was variable.…”
Section: Acceptability: Satisfaction and Qualitative Datamentioning
confidence: 99%
“…As their cognitive abilities decrease, persons with advanced dementia increasingly need to be in communion with carers to preserve their vulnerable self. Söderlund et al (71) reported positive results from using the Feil' s validation method during one-to-one conversations with persons with advanced dementia. The focus was not the facts about what was expressed but rather the feelings behind what the persons tried to talk about and the aim was to treat them as adults and increase their feelings of self-worth and well-being.…”
Section: Communicationmentioning
confidence: 99%
“…Today, nursing home residents tend to be older and more disabled than before (S€ oderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2016;Young, Barhydt, Broderick, Colello, & Hannan, 2010). The majority may also have cognitive impairment, which makes it difficult to interpret the older person's needs, wishes and symptoms (Condelius, Edberg, Jakobsson, & Hallberg, 2008;Dwyer, Gabbe, Stoelwinder, & Lowthian, 2014).…”
Section: Introductionmentioning
confidence: 99%